2019
DOI: 10.1038/s41598-019-43752-z
|View full text |Cite
|
Sign up to set email alerts
|

NO gas sensor based on ZnGa2O4 epilayer grown by metalorganic chemical vapor deposition

Abstract: A gas sensor based on a ZnGa 2 O 4 (ZGO) thin film grown by metalorganic chemical vapor deposition operated under the different temperature from 25 °C to 300 °C is investigated in this study. This sensor shows great sensing properties at 300 °C. The sensitivity of this sensor is 22.21 as exposed to 6.25 ppm of NO and its response time is 57 s. Besides that, the sensitivities are 1.18, 1.27, 1.06, and 1.00 when exposed to NO 2 (500 ppb), SO … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
46
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(49 citation statements)
references
References 47 publications
3
46
0
Order By: Relevance
“…In fact, thin film structures are more stable and reliable than one-dimensional nanostructures and better adhere to solid surfaces in practical devices. Wu et al discussed the gas sensor properties based on epitaxial ZnGa 2 O 4 thin film grown on sapphire substrate by MOCVD [13]. Tsai et al reported that the successful manufacture of deep-UV ZnGa 2 O 4 photodetectors and investigate the effect of annealing temperature on the devices electrical properties [14].…”
Section: Introductionmentioning
confidence: 99%
“…In fact, thin film structures are more stable and reliable than one-dimensional nanostructures and better adhere to solid surfaces in practical devices. Wu et al discussed the gas sensor properties based on epitaxial ZnGa 2 O 4 thin film grown on sapphire substrate by MOCVD [13]. Tsai et al reported that the successful manufacture of deep-UV ZnGa 2 O 4 photodetectors and investigate the effect of annealing temperature on the devices electrical properties [14].…”
Section: Introductionmentioning
confidence: 99%
“…Sensor measurements demonstrate that hybrid materials are able to detect NO at room temperature in the concentration range of 0.25-4.0 ppm with the detection limit of 69-88 ppb.Nanomaterials 2020, 10, 70 2 of 22 in noninvasive diagnosis of respiratory diseases [7][8][9]. In this case, the limitation of the quantitative determination of NO in exhaled air is due to the low level of its concentration (20-200 ppb) among a wide range of interfering gases [10].Direct determination of nitrogen monoxide in the gas phase is possible using conductometric gas sensors based on various semiconductor metal oxides [7,[10][11][12][13][14][15][16][17][18][19][20][21][22]. To increase selectivity of such analysis along with lower power consumption, complete or partial replacement of thermal heating with photoactivation is a promising approach.…”
mentioning
confidence: 99%
“…Direct determination of nitrogen monoxide in the gas phase is possible using conductometric gas sensors based on various semiconductor metal oxides [7,[10][11][12][13][14][15][16][17][18][19][20][21][22]. To increase selectivity of such analysis along with lower power consumption, complete or partial replacement of thermal heating with photoactivation is a promising approach.…”
mentioning
confidence: 99%
“…Wu et al [ 27 ] synthesized ZnGa 2 O 4 nanosheets which were able to detect NO, by using metal organic vapor deposition (MOCVD). Through SEM observation, it could be found that a layer of nanosheets was formed by the arrangement of spindle-shaped particles.…”
Section: Morphologymentioning
confidence: 99%